A Synthesis of the Chlorosulfolipid Mytilipin A via a Longest Linear Sequence of Seven Steps1. Issue 38 (8th August 2013) - Chung, Won‐jin; Carlson, Joseph S.; Bedke, D. Karl; Vanderwal, Christopher D.
<x xml:space="preserve">Abstract</x> Magnificent seven: The chlorosulfolipid mytilipin A was synthesized in racemic form in seven steps and in enantioenriched form in eight steps. Key transformations include a highly diastereoselective bromoallylation of a sensitive α, β‐dichloroaldehyde, a kinetic resolution of a vinyl epoxide, a convergent and highly Z‐selective alkene cross‐metathesis, and a chemoselective and diastereoselective dichlorination of a complex diene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>